2018
DOI: 10.1261/rna.064493.117
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sequencing of coding and noncoding RNA reveals a human transcriptome dominated by a small number of highly expressed noncoding genes

Abstract: Comparing the abundance of one RNA molecule to another is crucial for understanding cellular functions but most sequencing techniques can target only specific subsets of RNA. In this study, we used a new fragmented ribodepleted TGIRT sequencing method that uses a thermostable group II intron reverse transcriptase (TGIRT) to generate a portrait of the human transcriptome depicting the quantitative relationship of all classes of nonribosomal RNA longer than 60 nt. Comparison between different sequencing methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 71 publications
6
98
0
Order By: Relevance
“…mncRNA copy number ranges from a handful of copies, for some snoRNAs, to more than a hundred copies for certain tRNAs, and for 5S rRNAs, in various organisms including cows, rats and plants (Bermudez-Santana et al, 2010;Haeusler & Engelke, 2006;Michaud, Cognat, Duchene, & Marechal-Drouard, 2011;Wong, Abrahamson, & Nazar, 1984). Although many of the mncRNA copies might not be functional, a large number of these copies generate detectable RNA and in some cases, they are strongly expressed (Boivin, Deschamps-Francoeur, Couture, et al, 2018;Hoeppner, Denisenko, Gardner, Schmeier, & Poole, 2018).…”
Section: Expression Of Multicopied Mncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…mncRNA copy number ranges from a handful of copies, for some snoRNAs, to more than a hundred copies for certain tRNAs, and for 5S rRNAs, in various organisms including cows, rats and plants (Bermudez-Santana et al, 2010;Haeusler & Engelke, 2006;Michaud, Cognat, Duchene, & Marechal-Drouard, 2011;Wong, Abrahamson, & Nazar, 1984). Although many of the mncRNA copies might not be functional, a large number of these copies generate detectable RNA and in some cases, they are strongly expressed (Boivin, Deschamps-Francoeur, Couture, et al, 2018;Hoeppner, Denisenko, Gardner, Schmeier, & Poole, 2018).…”
Section: Expression Of Multicopied Mncrnasmentioning
confidence: 99%
“…In contrast, the 50–200 nucleotides size range includes several highly structured and highly expressed RNA families including transfer RNAs (tRNAs), small nuclear RNAs (snRNAs), and small nucleolar RNAs (snoRNAs; Boivin, Deschamps‐Francoeur, & Scott, ; Brosnan & Voinnet, ; Haeusler & Engelke, ; Iben & Maraia, ). These abundant highly structured families of “small” noncoding RNA share fundamental characteristics in terms of structure, maturation, and function that hinder their detection by RNA‐sequencing (Boivin et al, ). Some members of these small noncoding RNA families and other additional RNA groups (including some snoRNAs and snRNAs, as well as the 7SL, 7SK, and RNaseP RNAs) are longer than 200 nucleotides and are often categorized as long noncoding RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…GsI-IIC RT (TGIRT-III) has been used for a variety of applications, including comprehensive profiling of whole-cell, exosomal and plasma RNAs Qin et al 2016;Shurtleff et al 2017;Boivin et al 2018); quantitative tRNA-seq based on the ability of the TGIRT enzyme to obtain full-length end-to-end reads of tRNAs with or without demethylase treatment (Shen et al 2015;Zheng et al 2015;Qin et al 2016); determination of tRNA aminoacylation levels (Evans et al 2017); high-throughput mapping of posttranscriptional modifications by distinctive patterns of misincorporation (Katibah et al 2014;Zheng et al 2015;Shen et al 2015;Shurtleff et al 2017;Li et al 2017;Safra et al 2017); identification of protein-bound RNAs by RIP-Seq or CLIP (Katibah et al 2014;Zarnegar et al 2016); and RNA-structure mapping by DMS-MaPseq (Zubradt et al 2017;Wang et al 2018) or SHAPE (Mohr et al 2018). A study comparing TGIRT-seq to benchmark TruSeq v3 datasets of rRNA depleted (ribodepleted) fragmented Universal Human Reference (UHR) RNA with External RNA Control Consortium (ERCC) spike-ins showed that TGIRT-seq: (i) better recapitulates the relative abundance of mRNAs and ERCC spike-ins; (ii) is more strand-specific;…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, we show that the precision, quality and depth of transcriptome analysis can be greatly enhanced by carefully choosing and tuning read assignment tools using existing sequencing data. Modification of the read assignment pipeline for the analysis of a TGIRT-seq fragmented dataset, which provides an accurate view of the whole transcriptome (Boivin, et al, 2018) increased the proportion of assigned reads by 15% and modified the number of assigned reads for 50% of all expressed genes (Fig. 4, Supplementary Fig.12).…”
Section: Discussionmentioning
confidence: 99%